Examining the Effects of Cultural Context on Consumer Behavior - Saleh, Firman -; Hermansyah, sam (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2024)
Culture is a symbol as well as complex facts and symbols made by humans, passed down from generation to generation as determinants and regulators of human behavior in existing society. Cultural settings can be defined as multidimensional which plays an important role in every individual such as forming attitudes, beliefs, and individual behavior. Culture can be said as a comprehensive concept, and includes almost everything that influences the thinking process and individual behavior. This culture can be formed through classification based on certain categories such as nationality, religion, racial group, and geographical location. This study discusses matters such as the following, cultural Influences on purchasing decisions, dimension of culture, current trends in consumer culture, the influence of myths on marketing in the modern age, and the influence of a group or individual mode system.